Engineered nanomaterial in electronics and electrical industries - Nurul Akmal, Che Lah; Mohd N. M., Zubir; Mahendran, Samykano (Elsevier, 2018)
The explorations of the innovative properties of engineered nanomaterials specifically in electronics and electrical applications are not new and yet are progressing, particularly in the size-tuning-based assembly. Recently, the new approach in combining broad classes of dissimilar engineered materials into heterogeneous integrated electronic device systems with multiple dimensional layouts (e.g., nanotube, nanowires, and nanoribbons) has become one of the promising routes in yielding high-throughput performance integrated electronics on rigid and flexible device substrates. With different forms of engineered materials needed in everything from high-performance nanostructures to thin film electronic devices, it is crucial to understand the aimed needs of the application when considering new nanomaterial options. In this chapter, we thoroughly reviewed the current issues regarding engineered nanostructures and manufactured nanomaterials technologies in which their newness should evidently improve the classical margin and retention performance toward successful commercial deployment in nanoelectronic areas. Within the current blossoming era of functional layers of printed and flexible electronics, the review also featured particular focus on the soft engineered materials processing, competitive device fabrication and performance, reliability, and low-cost manufacturing as well as the status of commercialization upon suitable large-scale manufacturing routes. The significant impact on the engineered materials processes, product fabrications, and applications within flexible electronics are also highlighted.